New Issue Market in India: An Analysis of Growth Trends, Recent Development and Evaluation of Primary Issues - Rathore, G. S.; Pandey, Shyam Lal Dev (Indian Journal of Finance, 2008)
During current decade there has been remarkable reforms in the India Economic scenario. Consequently NIM has made enormous progress in recent years, moving away from fixed- price offering to price discovery through a screen-based auction for IPOs. This has reflected a quest to discover the price through an open fair, competitive auction, which is done in a fully transparent way, where all investors participate in an equal setting, and the investment bankers' or other influences do not vitiate the allocation of shares. The increase in fund mobilization from NIM in India has been exceptionally well. The rise in fund mobilized from Rs. 14042 crore in 1991-92 to Rs. 114577 crore is not a small achievement from any standard. Though some time unfair trade practices, IPO scam and political and economic instability has deteriorated the faith of retail investor in primary market. Now they need strong IPO analysis before investing their hard earned money. This paper is an effort to critically study the growth trends of NIM in India : category wise and ownership wise. Paper also insight the impact of IPO scam on the growth of NIM, recent effort of market regulator (SEBI) to make NIM efficient and transparent and throw light on the appropriate way to evaluating the primary issues.